Unravelling sprint hurdling performance: the biomechanical triad of block start efficiency, reaction time, and time to first touchdown - Gisladottir, T.; Hafsteinsson, T.; Petrovic, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The interplay between block start biomechanics, reaction time, and the time to first touchdown in 60m hurdles races is integral to unravelling the dynamics of sprint hurdling performance. A proficient start from the blocks sets the tone for the entire race, with reaction time directly influencing the athletes initial acceleration. Additionally, scrutinizing the biomechanical aspects of the time to first touchdown offers valuable insights into hurdling technique and race strategy, highlighting the intricate relationship among these key factors in achieving competitive success. METHODS: Data were obtained from the report of Nicholson et al. (2019), on 7 female and 8 male finalists of the IAAF World Championship in the 60m hurdles race held in March 2018 in Birmingham, UK. The following variables were analyzed and presented: reaction time, time to block exit, and time to first touchdown and ranking. RESULTS: In analyzing the data, it is evident that Harrison faced challenges across multiple key metrics, ranking last in block exit time, reaction time, and time to first touchdown. Despite being ranked first overall, Manning demonstrated remarkable efficiency by securing the top spot in all three categories. Notably, Pedersen showcased consistency, ranking joint seventh in reaction time while excelling with the sixth fastest block exit time and the third fastest time to first touchdown. In this women`s race, Eaton emerges as a standout performer, securing the second spot overall while boasting impressive rankings in both reaction time and time to block exit. Meanwhile, Pozzi demonstrated consistency by clinching the top spot in block exit time and maintaining a solid performance across other metrics, earning her first place overall. Notably, Martinot-Lagarde showcased a balanced approach, ranking consistently across all categories and securing the fifth position overall. CONCLUSION: The analysis reveals that superior sprint hurdling performance is characterized by athletes who demonstrate quick reaction times, efficient block exit transitions, and adapt handling of hurdles with minimal time to the first touchdown. Consistency across these variables underlines the importance of a well-rounded approach, with athletes like Manning and Pozzi showcasing prowess in balancing speed, technique, and strategy for optimal race execution. Overall, these findings emphasize the critical role of reaction time, block exit efficiency, and hurdling technique in determining success in sprint hurdling events. Particularly is the interesting case of Harrison, runner who had reaction time and time to block exit almost the slowest of all finalists but could manage to win the race. This example shows that there is always an exception to the rules.